Pengaruh Kepemimpinan Dan Kompetensi Terhadap Loyalitas Karyawan Patra Jasa Convention Hotel - Zulham Dwi Pratikto; Hari Susanta Nugraha (Universitas Diponegoro, 2017)
This research is motivated by the increasingly strict business world, this particular situation will surely create a competitive environment that will also demand every company to increase their performances by focusing on employees’ loyalty. One of the services that can be affected by current developmentishotel businesses. Hotel services become veryimportant because of the growth of potentially Indonesian tourism, therefore we need a service of a place to stay for tourist and that is called hotel. However, in the period of 2011-2016 there is fluctuation in the turnover of Patra Jasa Semarang Convention Hotel’s employees. If this is not addressed then it is feared that the hotel employees of Patra Jasa Convention Hotel can not meet the targets from company and making them increasingly lagging from other hotel services.The purpose of this study was to determine the effect of leadership and competency on Patra Jasa Semarang Convention Hotel. That method of this research is explanatory, with data collection through questionnaires and interviews. The sampling technique used saturated technique sampling withthe respondents of 100 people whom are employees of Patra Jasa Semarang Convention Hotel. The analysis technique used was quantitative. Quantitative analysis using validity, reliability, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test) and that being tested use SPSS for Windows 16.0 version.All independent variables,leadership (X1) and competency (X2) together (simultaneously) or individually (partial) affect independent variable of employees’ loyalty (Y). Advice that can be given to Patra Jasa Semarang Convention Hotel is that they need to give explanation, supervision, and monitoring of employees’ work thus they will always get motivated while working. Moreover, the company needs to give advance training to its employees and guidance given by the manager is also important, considering the standard of the company that changes according to market conditions at that time. Also the need for continued research by the company or outside the company regarding other variables that can provide additional contributions to improve employees’ loyalty.